Comparative rhizome anatomy of four species of Curcuma - UNNIKRISHNAN, P N RAVINDRAN, K K SHERLIJA, A B REMASHREE, K (Journal of Spices and Aromatic Crops, 1998)
The anatomy of rhizomes of four economically important species of Curcuma namely, C. longa (turmeric), C. aromatica (kasthuri turmeric), C. amada (mango-ginger) and C. zedoaria (yellow zedoary) were studied, Though all the species basically had similar anatomical characters, variations were nocticed in the number and arrangement of primary and secondary vascular bundles, orientation of endodermoid layer, number and shape of starch grains and curcumin cells. Maximum number and size of curcumin cells were found in C. longa. The endodermoid layer formed a continuous ring along with the pericycle in C. longa and was more or less circular in C. amada. But in C, aromatica and C. zednario, this layer was discontinuous and wavy in nature, In C. longa the meristematic layer was associated with true cambium with ray and fusiform initials, Apart from this, the number of compaoion cells was clirectly proportional to metabolic translocation and deposition of reserve substances which can be considered as identifying characters among the species.